PENERAPAN GAYA ARSITEKTUR MODERN TROPIS PADA PERANCANGAN TOKO KUE DAN BUKU DI SAMARINDA - Lalu Muhamad Gantara Ranusman; Upa, Keytysha Efifania; Rulia, Anna; Thamrin, Nur Husniah; Ramdhani, Iga Nur (Jurnal Kreatif : Desain Produk Industri dan Arsitektur, 2025)
Samarinda is developing City in the tourism industry, Specially in culinary tourism. Data shows that Samarinda has the second-highest number of restaurants in East Kalimantan after Balikpapan, its indicated by significant potential as a culinary tourism destination. This growth aligns with the increasing public interest in high-quality food and beverages, as well as the demand for comfortable reading spaces. Therefore, to accommodate both the high interest in reading and culinary tourism, a building concept that integrates these activities is necessary. This study aims to design an integrated concept of a bakery and bookstore in Samarinda, adopting a modern tropical architectural style. The design is expected to create a comfortable, aesthetic, and functional space that also reflects local identity. The design process is based on an analysis of the tropical climate and user needs. This research method uses a qualitative descriptive method, with this research method it is expected to show various qualitative information with careful description and analysis. Each object will be studied in terms of trends, non-uniformity, thought processes, object models and their integration as in the case study. The results of the study indicate that the proposed design successfully integrates a two-story bakery and bookstore using a modern tropical architectural approach in Samarinda. The adaptation of modern tropical architecture is reflected in the incorporation of elements such as sloped roofs, cross ventilation, sun shading, as well as the use of natural materials such as natural stone and wood.